2020
DOI: 10.1007/s00595-020-02175-4
|View full text |Cite
|
Sign up to set email alerts
|

Clinical outcomes of patients after nipple-sparing mastectomy and reconstruction based on the expander/implant technique

Abstract: Advances in multi-modality treatments incorporating systemic chemotherapy, endocrine therapy, and radiotherapy for the management of breast cancer have resulted in a surgical-management paradigm change toward less-aggressive surgery that combines the use of breast-conserving or -reconstruction therapy as a new standard of care with a higher emphasis on cosmesis. The implementation of skin-sparing and nipple-sparing mastectomies (SSM, NSM) has been shown to be oncologically safe, and breast reconstructive surge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 79 publications
0
4
0
Order By: Relevance
“…The study aims to evaluate the early outcomes after SSM and /or SNSM for BC or diagnosis of BRCA1/2 mutation followed by breast reconstruction with one- or two-stage technique. Clinical studies have demonstrated that performing immediate implant-based breast reconstruction after SSM and /or SNSM does not impact on post-operative recurrence, survival, or delayed diagnosis of recurrence [ 4 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The study aims to evaluate the early outcomes after SSM and /or SNSM for BC or diagnosis of BRCA1/2 mutation followed by breast reconstruction with one- or two-stage technique. Clinical studies have demonstrated that performing immediate implant-based breast reconstruction after SSM and /or SNSM does not impact on post-operative recurrence, survival, or delayed diagnosis of recurrence [ 4 , 5 , 7 ].…”
Section: Discussionmentioning
confidence: 99%
“…The explanation could probably be linked to the surgical complexity correlated to preserve an adequate thickness of subcutaneous flap due to previous breast scar. Moreover, patients with ipsilateral loco-regional recurrence after BCS plus radiotherapy are at higher risk of complications if underwent SSM and/or SNSM and immediate direct-to-implant technique [ 7 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mastectomy techniques are so improved to allow the skin and NAC preservation with the same oncological safety of simple mastectomies, where skin and NAC are removed [ 7 , 8 ]. Moreover, the postoperative complication rate of skin and NAC-sparing mastectomies is around 20–30%, needing a medical or surgical treatment in 10–12% of cases [ 9 ]. The most frequent complications are mastectomy skin flaps (MSF) necrosis, surgical site infection (SSI), the presence of a seroma and/or hematoma, and the implant removal, determining a reconstructive failure [ 10 ].…”
Section: Introductionmentioning
confidence: 99%